Juozas Baltūsis – the eminent mathematics teacher in the 20th–60th years of the 20th century in Lithuania - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2015)
Mathematics teacher Juozas Baltūsis (1900–1994) started his pedagogical activities in the 20th years of the 20th century and retired on a pension in the 70th years of the century. Within over 40-year period of his pedagogical activities, he taught many future mathematicians and engineers; he worked individually with gifted pupils and encouraged them to participate mathematical contests. The teacher took a great interest in integration of the teaching mathematics with the real life and other school subjects. In the prewar period, he compiled 3 course-books and in the postwar period – 3 papers; in the said works, he implemented the ideas on integration in practice.